Culture du paysage, gouvernance territoriale et mise en tourisme dans des montagnes rurales de l’Asie méridionale (Népal, Inde, Chine, Laos, Vietnam) - Évelyne Gauché; Steve Déry; Pierre Dérioz; Olivier Ducourtieux; Marie-Anne Germaine; Frédéric Landy; Maud Loireau; Laura Verdelli (Développement Durable et Territoires)
Five case studies are presented, all located in highland regions of South Asia and inhabited by ethnic minorities (India, Nepal, China, Laos, Vietnam), in order to analyze the consequences of narratives, actions and transformations of governance via the landscape. How does the landscape become, through tourism, a « way of seeing » territories, how does it foster renewed governance of these territories ? After having shown how the use of landscape resources leads to the development of a landscape culture via tourism, we will see that the landscape occupies various places in the processes of territorial governance. A final typology will be based on three criteria : consciousness of the landscape, governance process, and tourism expansion.